USER EXPERIENCE EVALUATION ON MUSIC STREAMING APPLICATIONS WITH UEQ METHOD - Angela Angela; Fandi Halim; Tri Agung Pramana; Andolin Simanjuntak (STMIK Royal, 2022)
Abstract: Along with the development of information technology, the way people listen to music also changed with the emergence of many music streaming applications. The user experience of an application plays an important role in attracting and retaining application users. Therefore, this study has goal to compare the music steaming applications’ user experience of the Joox and Spotify by using User Experience Questionnaire (UEQ) method. There are 6 scales assessed by UEQ, including attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data was collected by distributing online questionnaires and obtained as many as 104 responses that could be processed. The results show that both applications have positive impressions which are indicated by the average value of each scale greater than 0.8. This indicates that these two applications are considered quite fun, effective, easy to understand, and innovative. However, the comparison’ results show that between Spotify and Joox is not significantly different, with Spotify scores slightly better than Joox. Keywords: music streaming application; user experience; user experience questionnaire Abstrak: Seiring dengan perkembangan teknologi informasi, cara masyarakat mendengarkan musik juga mengalami perubahan dengan munculnya banyak aplikasi streaming musik. User experience suatu aplikasi berperan penting untuk menarik dan mempertahankan pengguna aplikasi. Oleh karena itu, penelitian ini memiliki tujuan untuk membandingkan user experience dari aplikasi streaming musik Joox dan Spotify dengan metode User Experience Questionnaire (UEQ). Terdapat 6 skala yang dinilai oleh UEQ yaitu daya tarik, kejelasan, efisiensi, ketepatan, stimulasi, dan kebaruan. Data dikumpulkan melalui penyebaran kuesioner secara daring dan diperoleh sebanyak 104 jawaban yang bisa diolah. Hasil penelitian menunjukkan bahwa kedua aplikasi memiliki impresi positif yang ditandai dengan nilai rata-rata setiap skala lebih besar dari 0.8. Artinya kedua aplikasi ini dinilai cukup menyenangkan, efektif, mudah dipahami, dan inovatif. Meskipun demikian, hasil perbandingan menunjukkan bahwa perbedaan antara Spotify dan Joox tidak terlalu signifikan, dengan nilai Spotify sedikit lebih unggul daripada Joox. Kata kunci: aplikasi streaming musik; pengalaman pengguna; user experience questionnaire